S02-5 Physical inactivity in nine Eastern European and Central Asian countries: results from the WHO STEPwise approach to NCD risk factor surveillance. (29th August 2022) - Whiting, Stephen; Mendes, Romeu; Abu-Omar, Karim; Gelius, Peter; Crispo, Anna; McColl, Karen; Simmonds, Phillipa; Fedkina, Natalia; Andreasyan, Dianne; Gahraman, Hagverdiyev; Migal, Tatyana; Sturua, Lela; et al.
Abstract: Background: Physical inactivity is a major risk factor for noncommunicable diseases. This paper explores patterns of physical inactivity in Armenia, Azerbaijan, Belarus, Georgia, Kyrgyzstan, Moldova, Tajikistan, Türkiye and Uzbekistan. Methods: Nationally-representative data were collected through the WHO STEPwise survey of noncommunicable disease risk factors, which utilizes the Global Physical Activity Questionnaire (GPAQ) to estimate population physical inactivity. Results: The prevalence of physical inactivity varied across the region, from 11.4 to 44.7%, and was higher among women than men in all countries except for Armenia, Belarus and Moldova. In most countries, the highest proportion of physical activity levels were registered during work time and appeared to vary according to the countries' level of development. For both sexes and across all populations, time spent on leisure or recreational physical activity was low. Conclusions: These results have important implications for policy, including actions to promote active travel and leisure-time physical activity as countries develop economically. Investments in workplace physical activity programmes and infrastructure are needed as populations transition to sedentary from more physically active occupations. The results reiterate the need for multisectoral policies, programmes and interventions to promote physical activity tailored to the local context.